DINAMIKA PSIKOLOGI DAN PERILAKU FORGIVENESS BAGI KORBAN KEKERASAN DALAM RUMAH TANGGA - Syarif Hidayatullah; Siti Hafsah Budi Argiati Hafsah Budi Argiati Argiati (Universitas Sarjanawiyata Tamansiswa, 2013)
AbstractThis research is to see how the dynamics of domestic violence victims psychological and behavioral Forgiveness developed. Research subjects are in use are the two people that took place in Yogyakarta.This research is a descriptive study using qualitative methods. The approach used in this study is phenomenology. With this method of data collection were extracted using observation and interviews. The analysis is conducted by applying the codes to the material obtained.Conclusions generated in this study the existence of distress as a result of domestic violence on both subjects. As a way to reduce the distress the two subjects did coping each using two types of coping, which focuses on the problem of coping and emotion focused coping.Key word: Behavioral Forgivenes, domestic violence.